The Influence of Participatory Leadership, Work Motivation, and Organizational Communication on Employee Performance Perumda Tirtanadi Berastagi Branch - Eka Novika Br Bukit; M. Chaerul Rizky; Darmilisani Darmilisani (Jurnal Multidisiplin Indonesia, 2026)
This study aims to determine the influence of participatory leadership, work motivation, and organizational communication on the performance of employees of PERUMDA Tirtanadi Berastagi Branch, both partially and simultaneously. The type of research used is quantitative research with an associative approach. The population in this study comprised all employees of PERUMDA Tirtanadi Berastagi Branch, with a sample of 38 respondents determined using a saturated sampling technique. The data collection technique employed a questionnaire based on the Likert scale, while the data analysis technique utilized multiple linear regression analysis with the assistance of SPSS software. The results of the study show that, partially, participatory leadership and work motivation have a positive but insignificant effect on employee performance, while organizational communication has a positive and significant effect on employee performance. Simultaneously, participatory leadership, work motivation, and organizational communication have a significant effect on employee performance. The coefficient of determination (R²) value of 0.356 indicates that 35.6% of the variation in employee performance can be explained by all three independent variables, while the remainder is influenced by other factors outside the research model. This study concludes that organizational communication is the dominant factor in improving the performance of employees of PERUMDA Tirtanadi Berastagi Branch